The Study of the Potential of Hmong Kiew Kan in Community Based Tourism Management - Pudwong, Hatsanai; Monpanthong, Paithoon (Dusit Thani College Journal, 2020)
This qualitative research contained two objectives which were (1) to survey tourism resources of Hmong Kiew Kan Village, and (2) to study the community based tourism management potential of Hmong Kiew Kan Village. The informants of this study included three key informant groups which were a state unit, private unit, and local people, with the total of 43 people. The tools were a semi-structured interview and participatory observation, and data were summarized by thematic analysis. The study result revealed that there is two type of tourism resources in Hmong Kiew Kan Village, the first is culture and local wisdom and the second is natural resource. Moreover, This study found that Hmong Kiew Kan community has potential to manage both mentioned tourism resources because there is participatory management of community-based tourism with government, private as well as local community.